PGNAA system preliminary design and measurement of In-Hospital Neutron Irradiator for boron concentration measurement. (December 2015) - Zhang, Zizhu; Chong, Yizheng; Chen, Xinru; Jin, Congjun; Yang, Lijun; Liu, Tong
Abstract: A prompt gamma neutron activation analysis (PGNAA) system has been recently developed at the 30-kW research reactor In-Hospital Neutron Irradiator (IHNI) in Beijing. Neutrons from the specially designed thermal neutron beam were used. The thermal flux of this beam is 3.08×10 6  cm −2  s −1 at a full reactor power of 30 kW. The PGNAA system consists of an n-type high-purity germanium (HPGe) detector of 40% efficiency, a digital spectrometer, and a shielding part. For both the detector shielding part and the neutron beam shielding part, the inner layer is composed of 6 Li2 CO3 powder and the outer layer lead. The boron-10 sensitivity of the PGNAA system is approximately 2.5 cps/ppm. Two calibration curves were produced for the 1–10 ppm and 10–50 ppm samples. The measurement results of the control samples were in accordance with the inductively coupled plasma atomic emission spectroscopy (ICP-AES) results. Highlights: A new PGNAA system in IHNI was described. It was for the first time that PGNAA system was used on neutron beam and realized the online measurement at IHNI. The boron-10 sensitivity of this system is around 2.5 cps/ppm, which is satisfied as the neutron flux is only 3.08E6/cm 2 /s 1 at full reactor power 30 kW. The measurement results were in accordance with ICP-AES results.